Risk Less and Prosper : Your Guide to Safer Investing - Bodie, Zvi and Taqqu, Rachelle, 1947- (Hoboken, New Jersey John Wiley and Sons, 2012)
BA practical guide to getting personal investing right/b Somewhere along the way, something has gone very wrong with the way individuals save and invest. Too often, households are drawn in by promotional suggestions masquerading as impartial investment advice. Consumers get saddled with more risk than they realize. Authors Zvi Bodie and Rachelle Taqqu understand the dilemma that today's investors face, and with iRisk Less and Prosper/i they will help you find your financial footing. Written in an accessible style, this practical guide skillfully explains why personal investing is all about you'your goals, your values and your career path. It shows how to understand investment risk and choose the particular blend of risk and safety that is right for you. And it lays out several simple yet powerful ways for small investors to cast a reliable safety net to achieve their financial goals and truly prosper. Coauthors Bodie and Taqqu challenge the myth that all investments require risk, then highlight some important risks that families often disregard when deciding where to put their money. Later, they connect the dots between investment and investor, showing us all how to grasp our own investment risk profiles and how we may use these insights to make more fitting investment choices.ulliOutlines a straightforward way to invest by aligning your investments with your goals and the risk levels you can bear/liliProvides basic investment abc's for readers who are otherwise literate/liliLays out a simple, actionable plan for achieving your goals/liliExplains the role of risk-free assets and investment insurance in assuring that you reach your most essential goals/i/li/ul Contrary to popular belief, investing doesn't have to be complicated. You can build wealth without taking great risks. iRisk Less and Prosper/i will show you how to make investment decisions that will make your financial life less stressful and more profitable
Include Index
Keywords: Risk -- Investments -- Finance, Personal